Enhanced oil recovery using hyperbranched polyglycerol polymer-coated silica nanoparticles - Wamda Faisal Elmobarak (17058024) (2021)
Functionalized Fe3O4–SiO2 magnetic nanoparticles (Fe–Si-MNPs) coated with hyperbranched polyglycerol polymer were prepared and tested for oil recovery from oil in water (O/W) emulsions. The structure, chemistry, and surface modifications of the newly developed demulsifier (PSiMNPs) were analyzed, and the percentage demulsification efficiency (%ηdem) was tested at differing concentrations of surfactant (Csur), oil (Coil), and demulsifier (DPSiMNPs). The developed PSiMNPs can be separated from the solution by a magnetic field, regenerated using ethanol, and reused several times. The reported %ηdem was ≥80% for all the studied Coil. The %ηdem improved as the Csur and pH decreased, with maximum values of 98.8% and 98.5% achieved at Csur = 0.05 g/L and a pH = 4, respectively. A DPSiMNPs = 100 mg/L was sufficient to achieve %ηdem of 99.4% for Coil = 100 mg/L and slightly decreased to ~93% for Coil ~4000 mg/L. The PSiMNPs can be reused up to 15 times with a steady %ηdem of 89.1% for Coil = 100 mg/L and 88.6% for Coil = 4000 mg/L. The adsorption of oil on the PSiMNPs follows Freundlich isotherm with maximum adsorption capacity (qmax) of 192.8 g/mg and Langmuir constant (b) of 28.06 mg/L for Coil = 900 mg/L. The qmax of the recycled PSiMNPs slightly decreased to 189.08 g/mg. The kinetic of oil recovery follows the PSO with a K2 of 0.0169 g/mg. min. Surface modification of Fe–Si-MNPs enhanced the oil adsorption, increased the adsorption capacity, and extended the service life resulting in a better cost and process feasibility. Other Information Published in: Chemosphere License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.chemosphere.2021.131295